Early diagnosis and treatment of Alzheimer’s disease: new definitions and challenges - Pais,Marcos (2020)
The prevalence of Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is expected to more than double by 2050. Studies on the pathophysiology of AD have been changing our understanding of this disorder and setting a new scenario for drug development and other therapies. Concepts like the “amyloid cascade” and the “continuum of AD,” discussed in this article, are now well established. From updated classifications and recommendations to advances in biomarkers of AD, we aim to critically assess the literature on AD, addressing new definitions and challenges that emerged from recent studies on the subject. Updates on the status of major clinical trials are also given, and future perspectives are discussed.